Linguistic intercomprehension in Peru: a diagnostic study - Llanto Chávez, Lilia Salomé (2012)
This work presents basic results but relevant cases of linguistic intercomprehension among related Amazonian and Andean languages in three specific contexts: confluence of Pano family languages, confluence of Arawak family languages and confluence of languages of Quechua family. To test the hypothesis, "... languages of the same language family share a basic grammatical organization which allows intercomprehension”, it has been initiated a pilot project with the Arawak languages. However, this process must continue in order to be able to determine if   the intercomprehension could be given just as other languages. The first results are positive in their application as teaching strategy in EIB.